2019
DOI: 10.1038/s41598-019-54759-x
|View full text |Cite
|
Sign up to set email alerts
|

Culture of Methanogenic Archaea from Human Colostrum and Milk

Abstract: Archaeal sequences have been detected in human colostrum and milk, but no studies have determined whether living archaea are present in either of these fluids. Methanogenic archaea are neglected since they are not detected by usual molecular and culture methods. By using improved DNA detection protocols and microbial culture techniques associated with antioxidants previously developed in our center, we investigated the presence of methanogenic archaea using culture and specific Methanobrevibacter smithii and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 67 publications
4
40
1
Order By: Relevance
“…Presence of M. smithii in the human gut is a feature of healthy lean adults while there is a depletion of this species in obese adults (Le Chatelier et al, 2013;Goodrich et al, 2014). In this context, M. smithii was less frequently detected by either culture or PCR in the milk samples obtained from obese mothers in the study of Togo et al (2019c). The human gastrointestinal tract is colonized by M. smithii early in life (Grine et al, 2017), and colostrum and milk may represent relevant sources of methanogenic archaea.…”
Section: The Composition Of the Human Milk Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of M. smithii in the human gut is a feature of healthy lean adults while there is a depletion of this species in obese adults (Le Chatelier et al, 2013;Goodrich et al, 2014). In this context, M. smithii was less frequently detected by either culture or PCR in the milk samples obtained from obese mothers in the study of Togo et al (2019c). The human gastrointestinal tract is colonized by M. smithii early in life (Grine et al, 2017), and colostrum and milk may represent relevant sources of methanogenic archaea.…”
Section: The Composition Of the Human Milk Microbiotamentioning
confidence: 99%
“…Some studies have identified archaeal sequences in human milk (Ward et al, 2013;Jimeńez et al, 2015;Togo et al, 2019c). In addition, Togo et al (2019b) were able to isolate Methanobrevibacter smithii from 3 colostrum and 5 milk samples out of a total of 20 samples while Methanobrevibacter oralis was cultured from one milk sample.…”
Section: The Composition Of the Human Milk Microbiotamentioning
confidence: 99%
“…Intriguingly, some recent reports have also detected the presence of Archaea in human milk or colostrum samples [ 19 ]. At present, the roles of those archaea in human milk are not well understood, and possibly some of them could be involved in weight regulation [ 66 , 67 , 68 ]. However, all these factors need to be further investigated, and it is of interest to further study the roles of Archaea in human milk and their transfer from human milk to the gut of breast-fed infants in our next study.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, methanogens gained interest in the clinical microbiology over the last years after methanogens have been detected by PCR-based methods and cultured from the gut microbiota (2,3); and their translocation in milk and urines has been further observed (4). Moreover, methanogens have been associated with dysbiosis such as in the case of vaginosis (5), urinary tract infections (6) and anaerobe abscesses of the oral cavity in the case of periodontitis and periimplantitis (7,8), in the case of refractory sinusitis (9), brain (10,11) and muscle (12).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the one-day newborns exhibited culturable Methanobrevibacter smithii (M. smithii) in the gastric fluid (20), suggesting a perinatal source of acquisition. Accordingly, we reported that mother milk did contain culturable M. smithii and culturable Methanobrevibacter oralis (M. oralis) (4). Yet, it is unclear whether these one-day methanogens do persist along with the digestive tract of the newborns or whether this is just one of several waves of acquisition of methanogens along the first months of the life (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%